2010
DOI: 10.3109/10799893.2010.506484
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of M2, M3, and M4muscarinic receptor expression in K562 chronic myelogenous leukemic cells by carbachol

Abstract: We showed that CCh-treatment leads to changes in muscarinic M(2), M(3), and M(4) receptor transcripts as well as M(2) and M(3) protein levels. We also found that CCh decreased proliferation of K562 cells in a time dependent manner, an effect prevented by atropine. These results suggest that CCh modulates K562 chronic myelogenous leukemic cells proliferation through muscarinic acetylcholine receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Relative protein expression levels of α7-nAChR and M3-mAChR were calculated from the band intensities using computerized densitometry with ImageQuantTL software (GE Healthcare Life Sciences) . Notably, the M3-mAChR immunoblot had two bands, which were considered and quantified as M3-mAChR in accordance with a previous study (19).…”
Section: Methodsmentioning
confidence: 79%
“…Relative protein expression levels of α7-nAChR and M3-mAChR were calculated from the band intensities using computerized densitometry with ImageQuantTL software (GE Healthcare Life Sciences) . Notably, the M3-mAChR immunoblot had two bands, which were considered and quantified as M3-mAChR in accordance with a previous study (19).…”
Section: Methodsmentioning
confidence: 79%
“…We found that exposure of K562 cells supplemented with 10% serum to CCh led to an inhibition of DNA synthesis [3] and a decrease in cyclin D 1 expression. Inhibition of cyclin D 1 expression was fully reversed by the muscarinic antagonists atropine (non-selective), gallamine (M 2 /M 4 selective) and tropicamide (M 4 selective) but not by 4-DAMP (M 3 selective).…”
Section: Discussionmentioning
confidence: 90%
“…We have previously demonstrated the presence of M 2 , M 3 and M 4 mAChRs and M 3 subtype mediated NO signaling in K562 chronic myelogenous leukemic cells [8]. We also showed that collagenase clostridium histolyticum (CCh)-treatment leads to changes in muscarinic M 2 , M 3 and M 4 receptor transcripts as well as M 2 and M 3 protein levels [3] and enhances cyclic adenosine monophosphate (cAMP) accumulation in these cells [21].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that many components of cholinergic signaling including Ach are present in a variety of non-neuronal tissues, such as lung cancer (21,22), colon (23), breast, ovarian carcinomas (24,25) and other common cancer cells. Interestingly, cholinergic signaling were found to increase further in the local tumor environment, representing a potential new pathway to target tumor growth (26).…”
Section: Discussionmentioning
confidence: 99%